Indonesia’s Spice-Based Gastrodiplomacy: Australia and Africa Continents as the Potential Markets - Yayusman, Meilinda Sari; Mulyasari, Prima Nurahmi (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2024)
The history of the spice route has left a legacy in Indonesia and the rest of the world. To date, Indonesia continues to be a major global player in the spice trade. Pepper, nutmeg, cloves, mace, and cinnamon were the country’s primary exports. Food may foster cross-cultural understanding, which can enhance international cooperation and engagement. Thus, foods rich in spices can be an asset for Indonesia’s gastrodiplomacy. In collaboration with various non-state actors and coordinated by Indonesia‘s Coordinating Ministry of Maritime and Investment Affairs, the Indonesian government has developed an ambitious gastrodiplomacy strategy called ”Indonesia Spice Up the World” (ISUTW). Despite possible hurdles, Australia and Africa could be potential markets for further implementation of ISUTW. The research aims to answer the following questions: 1) To what extent has Indonesia promoted its spice-based gastrodiplomacy? and 2) What are the opportunities and challenges of Indonesia‘s spice-based gastrodiplomacy for the Australian and African markets? The research employs a mixed-method approach, including surveys to gather data about Indonesian cuisine businesses operating in Australia. This research incorporates a literature analysis, in-depth interviews, and focus group discussions with both state and non-state actors to strengthen the study, particularly in the context of the African market. Indonesia's gastrodiplomacy strategy, centered around spices, is suggested to prioritize Australia and Africa by leveraging cultural connections and existing market presence to effectively promote Indonesian gastronomy globally.